\(\displaystyle{4}{\left({\cos}^{{2}}\right)}{x}-{3}={0}\)

\(\displaystyle{4}{\left({\cos}^{{2}}\right)}={3}\)

\(\displaystyle{\left({\cos}^{{2}}\right)}{x}=\frac{{3}}{{4}}\)

\(\displaystyle{\cos{{x}}}=\frac{{\sqrt{{3}}}}{{2}}\)

\(\displaystyle{x}={{\cos}^{{-{{1}}}}{\left(\frac{{\sqrt{{3}}}}{{2}}\right)}}\)

x=30

\(\displaystyle{4}{\left({\cos}^{{2}}\right)}={3}\)

\(\displaystyle{\left({\cos}^{{2}}\right)}{x}=\frac{{3}}{{4}}\)

\(\displaystyle{\cos{{x}}}=\frac{{\sqrt{{3}}}}{{2}}\)

\(\displaystyle{x}={{\cos}^{{-{{1}}}}{\left(\frac{{\sqrt{{3}}}}{{2}}\right)}}\)

x=30